Application Analysis of Small Braking Control for Subway Train Special Line - HE Yuqin; ZHANGYong; ZHANG Qian (机车电传动)
In view of the special track conditions, the application of the small braking control strategy was expounded from adhesive demand, control mode, the signal source, the speed limit value and logic circuit. With a detailed analysis of the feasibility and reliability of using pure air brake and pure electric braking mode, the small braking control strategy was indicated be reasonable and effective.